Islam in a World of Diverse Faiths
XVIII, 218 p.
Keywords: Today the Islamic faith has exploded on the contemporary scene. On television and in newspapers Islam is depicted as playing a major role in world events. In this illuminating volume distinguished Muslim, Christian and Jewish writers explore the nature of the Islamic religion and its impact on a pluralistic society. In diverse ways they present a new and challenging vision of dialogue between the three monotheistic faiths in the modern world.